“El espíritu de Marburgo” recorre la Estética operatoria. Luis Juan Guerrero, lector “evolutivo” de Heidegger - Belgrano, Mateo (Pontificia Universidad Católica del Perú, 2023)
“The Spectre of Marburg’ wanders around the Operative Aesthetics. Luis Juan Guerrero, ‘Evolutive’ Reader of Heidegger”. This paper aims to analyse the reading of Martin Heidegger’s thought offered by Luis Juan Guerrero in his Operative Aesthetics. I claim that “The Origin of the Work of Art” plays a central role in the work of the Argentinian philosopher. However, this does not mean that Guerrero is not an original author or that he is a mere commentator of the German philosopher. On the contrary: the Argentinian philosopher offers a productive reading of Heidegger which allows him to build his own and authentic philosophy. By focusing on Heidegger’s essay on art and on the first volume of the Operative Aesthetics, this paper analyses three essential issues: the concept of tool, the world-earth relationship, and the bond between history and truth.

En el presente trabajo nos proponemos analizar la lectura de Martin Heidegger en la Estética operatoria por parte de Luis Juan Guerrero. La tesis a defender consiste en que “El origen de la obra de arte” tiene un rol central en la obra del filósofo argentino. Pero esto no quiere decir que Guerrero no sea un autor original o que sea un mero comentador del filósofo alemán, sino todo lo contrario: el filósofo argentino hace una lectura productiva de Heidegger a partir de la cual elabora una filosofía propia y auténtica. Centrándonos en el ensayo sobre el arte de Heidegger y el primer tomo de la Estética operatoria, analizaremos tres puntos neurálgicos: el concepto de útil, la relación mundo y tierra y el vínculo entre historia y verdad.
“‘The Spectre of Marburg’ wanders around the Operative Aesthetics. Luis Juan Guerrero, ‘Evolutive’ Reader of Heidegger”
Keywords: Aesthetics; Work of art; World; History; Tool; Estética; Obra de arte; Mundo; Historia; Útil; https://purl.org/pe-repo/ocde/ford#6.03.01